Kesiapan Belajar Peserta Didik Melalui Pembelajaran Berdiferensiasi dalam Pembelajaran di Kelas - Enno Triandini (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
Education plays an important role in developing students' potential to be able to face challenges in the modern era. One approach that can increase the effectiveness of learning is differentiated learning, which adapts the learning process to the readiness, interests, and learning styles of students. This study aims to understand the application of differentiated learning in Mathematics subjects for grade VII A of junior high school and its impact on student learning outcomes. This study uses a qualitative method with a case study approach, involving observation, interviews, and document analysis. The results of the study show that teachers apply the stages of differentiated learning, such as diagnostic assessments, mapping learning readiness, and designing and implementing learning that is in accordance with student needs. In addition, it was found that this approach has a positive impact on student learning outcomes and motivation. The Merdeka Curriculum is considered more effective in supporting the implementation of differentiated learning compared to the previous curriculum. Thus, differentiated learning has proven to be an effective strategy in meeting student learning needs optimally. However, its implementation requires thorough preparation and flexibility from teachers to manage diversity in the classroom.